The welfare orientations of immigrant domestic workers in Greece - Psimmenos, Iordanis (The Greek Review of Social Research, 2011)
The language of welfare reflects not only life chances and redistributive practices that reduce income risks, but also occupational norms and welfare orientations. The article examines the case of immigrant domestic workers and how they relate to state welfare services. Through a reappraisal of the social significance of their job, it is argued that women workers are not only pushed but also pulled by a rising work culture which establishes a life into the margins of state welfare.1 The findings indicate that after a period of at least ten years in Greece and despite their legal entry or periodic legalisation in the country, their stable employment and their initial attempts to register with state welfare agencies, domestic workers are gradually distancing themselves from formal social insurance schemes. In addition to the existing analyses on the subject, it is suggested here that apart from work conditions, job customs and values seem also to reinforce welfare orientations that are more in line with paternalistic, informal and personality-based understandings and strategies of care. 1. The analysis reconsiders the findings based on a National Research (PYTHAGORAS I) project titled “Gender and Migrant Populations: aspects of Social Inclusion and Social Policy” implemented by the Centre of Social Morphology and Social Policy of the Panteion University of Social and Political Sciences under the general supervision of Emeritus Professors: K. Kassimati and L.M. Moussourou. For further details see The Greek Review of Social Research, 124, C/, 2007, as well as the analysis followed in Psimmenos and Skamnakis (2008), Psimmenos (2007) and Psimmenos (2010).